Physiological and methodological aspects of rate of force development assessment in human skeletal muscle - Rodríguez‐Rosell, David; Pareja‐Blanco, Fernando; Aagaard, Per; González‐Badillo, Juan José (Clinical physiology and functional imaging, 2018)
Summary Rate of force development (RFD) refers to the ability of the neuromuscular system to increase contractile force from a low or resting level when muscle activation is performed as quickly as possible, and it is considered an important muscle strength parameter, especially for athletes in sports requiring high‐speed actions. The assessment of RFD has been used for strength diagnosis, to monitor the effects of training interventions in both healthy populations and patients, discriminate high‐level athletes from those of lower levels, evaluate the impairment in mechanical muscle function after acute bouts of eccentric muscle actions and estimate the degree of fatigue and recovery after acute exhausting exercise. Notably, the evaluation of RFD in human skeletal muscle is a complex task as influenced by numerous distinct methodological factors including mode of contraction, type of instruction, method used to quantify RFD, devices used for force/torque recording and ambient temperature. Another important aspect is our limited understanding of the mechanisms underpinning rapid muscle force production. Therefore, this review is primarily focused on (i) describing the main mechanical characteristics of RFD; (ii) analysing various physiological factors that influence RFD; and (iii) presenting and discussing central biomechanical and methodological factors affecting the measurement of RFD. The intention of this review is to provide more methodological and analytical coherency on the RFD concept, which may aid to clarify the thinking of coaches and sports scientists in this area.